Differential responses of Bolivian timber species to prescribed fire and other gap treatments - Kennard, D.K.; Putz, F.E. (2005)
The article followed the establishment and growth response of 13 commercial tree species to canopy opening, above-ground biomass removal, and experimental burns of low and high intensities in a lowland dry forest in Bolivia. Three patterns of response to treatments were observed among the most abundant commercial tree species. (1) Shade-intolerant species regenerated mostly from seed and had the highest survival and growth rates following high-intensity burns. (2) Shade-tolerant species were abundant in gap control and plant removal treatments. Treatments had little effect on the height growth of these species. (3) Individuals of root sprouting species were most abundant following plant removal and low-intensity burn treatments. Treatments had little effect on the height growth of these species. The wide variation in species responses to gap treatments found in this study not only reinforces the concept that species are distributed along a continuum of shade-tolerance levels, but that other aspects of species biology, such as seed dispersal type or sprouting behavior, further differentiate regeneration strategies. The variety of regeneration strategies found among the species at this forest site will require a flexible management scheme that mixes more intensive silvicultural treatments such as prescribed burning with less intensive treatments.